Are Fe based catalysts an upcoming alternative to Ni in CO2 methanation at elevated pressure?. Issue 39 (July 2020) - Franken, Tanja; Heel, Andre
Highlights: Investigation of Fe-based methanation catalyst at elevated pressure. Low Fe loading and small Fe particles generate high CH4 yield. Foundation established for high competitiveness of Fe versus Ni based catalysts. Abstract: The raise of regenerative but unsteadily produced energy demands a highly flexible way to store the energy for time periods when less energy is produced than consumed. In the current study, it is investigated if catalysts based on environmentally more attractive and less hazardous to health Fe might be able to be considered as an alternative to Ni catalysts in the CO2 methanation at elevated pressure. For this a set of catalysts with 1–10 wt % Fe supported on the zeolite 13X is analysed in CO2 methanation at 1–15 bar. The trends of activity as well as selectivity with varying Fe loading and pressure are presented. Correlation with thorough characterization of the materials shows that a very high dispersion of Fe in octahedral sites within the zeolite is necessary to generate CH4 as the main reaction product and suppress the Fischer–Tropsch activity towards CC coupling reactions at elevated pressure. Especially with low Fe loading such as 1 wt % high reaction rates of 42 mmol(CO2 )/(mol(Fe)∙s) with a CH4 selectivity of 76 % at 300 °C and 10 bar are obtained. In contrast to that, highly Fe loaded catalysts tend to form increasing amounts of Fischer–Tropsch products at increasing pressure. In addition, highly Fe-loaded catalysts are much more susceptible to destruction of the zeolite under reaction conditions. At the same time, highly loaded catalysts form a Fe3 C shell around the remaining support. Hence, avoiding the formation of a Fe3 C phase is crucial for high CH4 selectivity. The results presented here therefore show that catalysts with a very high Fe-dispersion in particular can gain considerably in importance as alternatives to Ni-methanation catalysts at elevated pressure.